2016
DOI: 10.1002/adom.201600214
|View full text |Cite
|
Sign up to set email alerts
|

Solvothermal Synthesis and Ultrafast Photonics of Black Phosphorus Quantum Dots

Abstract: active photo electronic response, [18][19][20][21][22] with some emerging applications such as transistors and photodetectors devices. [23][24][25][26][27] Meanwhile, BP is used in vapor sensor, drug delivery, and cellular tracking systems because of its sensitivity and low toxicity. [28][29][30][31] Mechanical and liquid exfoliation methods have been adopted to prepare BP nanosheets with different numbers of layers and sizes. [32][33][34] Due to thickness-dependent bandgap structure of BP which is tunable ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
111
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 354 publications
(112 citation statements)
references
References 57 publications
1
111
0
Order By: Relevance
“…The band structure was to be considered in terms of few-layer BP without any quantum confinement effect. The saturation intensity was obtained using the saturation model in our previous work [7] and it was about 300 GW/cm 2 at 1030 nm, much larger than that of BP QDs (only 3.3 GW/cm 2 at 800 nm) but in the same order of magnitude with Xu et al (535.3 GW/cm 2 at 800 nm) and Lu's results (647.7 ± 60 at 800 nm) about BP nanosheets [4,30]. The Q-switching operation of BP saturable absorber has been demonstrated.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…The band structure was to be considered in terms of few-layer BP without any quantum confinement effect. The saturation intensity was obtained using the saturation model in our previous work [7] and it was about 300 GW/cm 2 at 1030 nm, much larger than that of BP QDs (only 3.3 GW/cm 2 at 800 nm) but in the same order of magnitude with Xu et al (535.3 GW/cm 2 at 800 nm) and Lu's results (647.7 ± 60 at 800 nm) about BP nanosheets [4,30]. The Q-switching operation of BP saturable absorber has been demonstrated.…”
Section: Resultssupporting
confidence: 61%
“…It can be seen that although the FOM decreases slightly with the size at 1030 nm, it is still in the same order of magnitude with that at 515 nm, indicating that BP is a good broadband saturable absorber. Xu et al prepared the BP quantum dots by solvothermal synthesis and found that the SA property is much better than that of BP nanosheets [30]. The average lateral size of the BP QDs is only about 2.1 ± 0.9 nm, in which the quantum confinement effect might be dominant.…”
Section: Resultsmentioning
confidence: 99%
“…SA technology is presently predominated by semiconductor saturable absorber mirrors (SESAMs). [31][32][33] To date, carbon nanotubes (CNTs), [34,35] graphene, [36,37] MoS 2 , [38,39] WS 2 , [40] topological insulators (TIs) [41][42][43][44] and black phosphorus [45][46][47] have been successfully utilized as SA for the realization of mode-locking. Ultrashort pulses can be used in many areas, such as optical communication and spectroscopy.…”
Section: Wwwadvancedsciencenewscom Wwwlpr-journalorgmentioning
confidence: 99%
“…A, Schematic diagram of the synthesis process of BPQDs prepared by solvothermal method. Reproduced with permission . Copyright 2016, Wiley‐VCH.…”
Section: Low‐dimensional Semiconductor Nanomaterialsmentioning
confidence: 99%